Scholarly activity in Canadian Residency Matching Service criteria: Do Canadian programs really care about applicant research? - El Galad, Asil; Van Dierdonck, Hanna; Chander, Nikesh; Mathai, Caleb; Palmateer, Alyssa; Dunn, Shenna; Weera, Seddiq; Chambers, Larry W; Bell, Amanda (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2026)
Background: Residency programs across Canada evaluate applicants based on written applications, reference letters, and interviews. One key factor many institutions consider is “scholarly activity.” To improve transparency, the Canadian Residency Matching Service (CaRMS) recently revised its program description pages, adding a dedicated section outlining expectations for research and academic work. This study examines whether these changes have made program criteria clearer for applicants.Methods: For all 17 Canadian faculties of medicine, 2023 R1 entry, —internal medicine, family medicine, pediatrics, general surgery, psychiatry and anesthesiology—program descriptions were reviewed on the CaRMS website, looking for keywords related to scholarly activity.Results: Although most residency programs now include scholarly activity in their CaRMS descriptions, several programs provide vague descriptions of this requirement. In 2023, nearly all family medicine (94%), internal medicine (100%), and pediatrics (100%) program descriptions referenced requiring or considering scholarly work as part of their selection process—up from 41%, 65%, and 71% in 2019. Programs commonly mentioned scholarly activity in two or three sections of their selection criteria, with key themes including active scholarly work, scholarly deliverables, and future scholarly potential.Conclusion: Canadian medical schools should set clearer expectations for scholarly activity in residency applications to ensure transparency and equal opportunities for all applicants. Programs could also explain why research matters—whether as a core component of training or to develop critical thinking and initiative. Greater clarity would help applicants see research as more than just a “check-the-box” requirement, fostering genuine engagement in scholarly work.